FLT3 mutations in myelodysplastic syndrome and chronic myelomonocytic leukemia1. Issue 1 (31st October 2012) - Daver, Naval; Strati, Paolo; Jabbour, Elias; Kadia, Tapan; Luthra, Raja; Wang, Sa; Patel, Keyur; Ravandi, Farhad; Cortes, Jorge; Qin Dong, Xiao; Kantarjian, Hagop; Garcia‐Manero, Guillermo
Abstract FMS‐like tyrosine kinase III (FLT3) mutations occur in one‐third of acute myeloid leukemia (AML) patients and predict poor outcome. The incidence and impact of FLT3 in myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia (CMML) is unknown. We conducted a retrospective review to identify WHO MDS and CMML patients with FLT3 mutations at diagnosis. A total of 2, 119 patients with MDS and 466 patients with CMML were evaluated at MD Anderson between 1997 and 2010. Of these, FLT3 mutation analysis was performed on 1, 232 (58%) MDS and 302 (65%) CMML patients. FLT3 mutations were identified in 12 (0.95%) MDS patients: 9 (75%) had FLT3‐ITD mutation and 3 had FLT3‐tyrosine kinase domain (TKD) mutation. MDS patients with FLT3 mutations were younger (P = 0.02) and presented as RAEB (P = 0.03) more frequently. Median overall survival (OS) for FLT3‐mutated MDS patients was 19.0 months versus 16.4 months for FLT3‐nonmutated MDS patients (P = 0.08). FLT3 mutations were identified in 13 (4.3%) CMML patients: 8 had FLT3‐ITD mutation and 5 had FLT3‐TKD mutation. There were no significant differences in demographic and disease characteristics among CMML patients with and without FLT3 mutations. Median OS for FLT3‐mutated CMML patients was 10.8 months versus 21.3 months for FLT3‐nonmutated CMML patients (P = 0.12). FLT3 occurs in MDS and CMML at a lower frequency than AML and does not predict poor outcome. Am. J. Hematol. 2013. © 2012 Wiley Periodicals, Inc.